2022
DOI: 10.1073/pnas.2115900119
|View full text |Cite
|
Sign up to set email alerts
|

Online engagement with 2020 election misinformation and turnout in the 2021 Georgia runoff election

Abstract: Following the 2020 general election, Republican elected officials, including then-President Donald Trump, promoted conspiracy theories claiming that Joe Biden’s close victory in Georgia was fraudulent. Such conspiratorial claims could implicate participation in the Georgia Senate runoff election in different ways—signaling that voting doesn’t matter, distracting from ongoing campaigns, stoking political anger at out-partisans, or providing rationalizations for (lack of) enthusiasm for voting during a transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 74 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…As the earlier literature review noted, democracy influences political participation, which influences the political outcome. Green and others (2022) and Kratou and Laakso (2022) emphasized that governments that ensure democracy and freedom to the citizens receive trust, which, in any case during elections, would not receive criticism on whether the elections are corrupt or not. This section tests the third hypothesis presented in the last section of the literature review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the earlier literature review noted, democracy influences political participation, which influences the political outcome. Green and others (2022) and Kratou and Laakso (2022) emphasized that governments that ensure democracy and freedom to the citizens receive trust, which, in any case during elections, would not receive criticism on whether the elections are corrupt or not. This section tests the third hypothesis presented in the last section of the literature review.…”
Section: Resultsmentioning
confidence: 99%
“…This argument is further backed by Kelly and Cook (2011) who argued that, even though freedom of communication is controlled and restricted, it still contributes to political participation and a fair electoral process in Africa. Nevertheless, according to Green and others (2022) and Kratou and Laakso (2022), false propaganda spread in the name of expressing freedom of communication has to be restricted for better political outcomes. In the African context, I expect freedom of expression to increase political participation, which is hypothesized to positively influence fair elections, given that most African countries since the turn of the 21st century have employed external organizations to supervise elections to ensure transparency and fair electoral outcomes.Hypothesis Freedom of communication positively moderates the effect of political participation on electoral outcomes in Africa.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Observational studies that capture naturally-occurring exposures similarly point to significant but limited effects of misinformation. Green et al (2022) examined misinformation exposure on Twitter. They found that people who engaged with conspiracy theories were likelier to vote, suggesting that, at least on Twitter, online exposure can have downstream effects on important political outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Misinformation can also threaten core civic processes. Exposure to false claims about politics discourages voter turnout (Green et al, 2022), produces a less-informed citizenry (Morgan et al, 2021), and erodes confidence in democracy itself (Ognyanova et al, 2020;Dahlke & Hancock, 2022).…”
Section: Introductionmentioning
confidence: 99%